2020
DOI: 10.1016/j.vas.2020.100101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sexed semen on different production and functional traits in German Holsteins

Abstract: Highlights Calf sex had an influence on calving ease and dystocia rates. Sexed semen within same calf sex had only minor effects on most traits. Stillbirth rate for the few male calves from semen sexed for females was 30.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(71 reference statements)
0
6
0
1
Order By: Relevance
“…Deliveries resulting in the birth of a bull calf accounted for 15.9%, including 3.2% stillbirths. In a study by Diers et al [2020], the percentage of heifers born following insemination with conventional semen was 52.7%, compared to 87.0% in the case of sexed semen. Lower ef- fectiveness for sexed semen was obtained in a study by Osada et al [2019], in which the percentage of deliveries resulting in the birth of a heifer was 73.8%.…”
Section: Resultsmentioning
confidence: 95%
“…Deliveries resulting in the birth of a bull calf accounted for 15.9%, including 3.2% stillbirths. In a study by Diers et al [2020], the percentage of heifers born following insemination with conventional semen was 52.7%, compared to 87.0% in the case of sexed semen. Lower ef- fectiveness for sexed semen was obtained in a study by Osada et al [2019], in which the percentage of deliveries resulting in the birth of a heifer was 73.8%.…”
Section: Resultsmentioning
confidence: 95%
“…In our study, cows inseminated with sexed semen had higher milk yields. However, Diers et al (21) reported that the milk yield of cows inseminated with conventional semen was 200 kg higher than cows inseminated with sexed semen. Postpartum body weights of dams giving birth to female calves were higher than giving birth to male calves.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, giving calving assistance may also increase the likelihood of trauma and contamination of the reproductive tract and increase the risk of endometritis infections. Farmers can reduce the risk of dystocia by using sexed semen from sires with calving ease and low percent stillbirths to produce female calves [38].…”
Section: Discussionmentioning
confidence: 99%